To find the y-intercept, let x = 0.
0 - 3y = -6
-3y = -6
y = 2
The y-intercept of the equation is the point (0, 2).
Answer:
log(x^7·y^2)
Step-by-step explanation:
The applicable rules are ...
... log(a^b) = b·log(a)
... log(ab) = log(a) +log(b)
_____
The first term, 7log(x) can be rewritten as log(x^7). Note that an exponentiation operator is needed when this is written as text.
The second term 2log(y) can be rewritten as log(y^2). These two rewrites make use of the first rule above.
Now, you have the sum ...
... log(x^7) +log(y^2)
The second rule tells you this can be rewritten as ...
... log(x^7·y^2) . . . . . seems to match the intent of the 3rd selection
Six thirty-five...............................
Answer:
<u>No solution it IS STUPID.</u>
Step-by-step explanation:
I don’t know for sure but maybe 60?